Optimized Cultivation of Stropharia rugosoannulata Using Winter Jujube Wastes and Safety Risk Assessment of the Cultivated Mushrooms - Jiale Yang; Shuguang Sun; Shuqin Qiao; Xinxin Li; Guorong Yu; Wenzhong Lan; Li Ji; Yupeng Ge; Xianhao Cheng; Weihuan Li (Horticulturae)
Substantial agricultural waste, including winter jujube residues, pits, and sawdust, is generated during the planting and processing of winter jujubes. To recycle these wastes, they were used to cultivate Stropharia rugosoannulata. The nutrient composition, mineral elements, 179 pesticide residues, and heavy metals in the wastes and S. rugosoannulata were tested. Cultivating the liquid spawn of S. rugosoannulata with 40 g/L winter jujube residue as a substitute for glucose significantly increased the mycelial pellets’ biomass by 136%, resulting in more uniform pellets. Secondary strains of S. rugosoannulata were cultured using winter jujube pits, showing no significant difference in mycelial growth rate and vigor compared to the control (CK) across additive levels of 10–30%. The fruit bodies of S. rugosoannulata cultivated with winter jujube sawdust exhibited no detectable pesticide residues and a lower heavy metal content than the allowable limits, with a protein content of 36.7 g/100 g. Additionally, the mineral element potassium surpassed sodium by over 200 times, rendering it a potassium-rich, low-sodium food source. Utilizing winter jujube wastes for S. rugosoannulata cultivation effectively repurposed these wastes through sustainable recycling. This approach not only reduces cultivation costs but also yields safe and nutritious edible fungal products.